Mechanism of action of Taohong Siwu decoction in the alleviation of primary dysmenorrhea - Zhou, Qixiu; He, Mei; Jin, Qiong; Gao, Shijia; Yang, Zhuya; Zhu, Peifeng; Tan, Wenhong; Liu, Lu (Frontiers in Medicine, 2024)
Background: As one of the most common gynecological disorders, PD significantly impacts the quality of life for women. TSD, a well-known traditional Chinese medical prescription, has gained popularity for its use in treating gynecological cold coagulation and blood stasis syndromes such as PD. However, the lack of comprehensive data hinders our understanding of its molecular mechanism. Purpose: The objective of the present study is to investigate the therapeutic effects of TSD on PD and elucidate its plausible mechanism. Methods: HPLC was employed to confirm the presence of the principal metabolites of TSD. The rat model of PD was induced by OT exposure following IWM and EB pretreatment, and subsequently treated with TSD via gastric gavage. The effects and potential mechanisms of TSD on PD rats were explored, encompassing general behavior, morphological alterations in the uterus and ovaries, biochemical indicators in the uterus and serum, and levels of proteins related to the PI3K/AKT signaling pathway. Results: Gallic acid, hydroxysafflower yellow A, albiflorin, paeoniflorin, and ferulic acid were determined to be the primary active metabolites of TSD. The pharmacological studies yielded results indicating the successful establishment of the PD model in rats. Additionally, TSD demonstrated its ability to protect PD rats by ameliorating general behavior, mitigating pathological damage to uterine and ovarian tissues, and modulating the expression levels of correlated factors (PGE2, PGF2α, Ca2+, TXB2, IL-6, TNF-α, NO, and COX-2) as well as p-PI3K/PI3K and p-AKT/AKT proteins. Conclusion: TSD exhibited protective effects against PD in rats through its interaction with multiple targets including P13K/AKT signaling pathway, indicating that TSD holds therapeutic potential for PD treatment and providing evidence supporting the rational utilization of TSD.